2016
DOI: 10.1515/geo-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of the Midia Port - Black Sea (Romania), on the coastal sediment quality

Abstract: Abstract:The aim of the study was to evaluate the impact of potential pollution sources, mainly from the upstream anthropogenic sources and port-related activities. The investigated area covered a wide range of anthropogenic impacts (e.g., industrial wastes, storm water runo , accidental oil spills, intentional discharges and shipping activities). The quality of water and sediments was assessed using standard methods, as physical-chemical parameters, chemistry and biology (microbiology, ecotoxicology) aiming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…1881/2006 [ 49 ], and there are no concerns about their consumption, especially when calculated hazard quotients were below the critical value 1 for all analyzed heavy metals, meaning no possible risks are associated with mussel consumption from the study areas. However, Pb concentrations in mussel meat samples taken from area 3 have slightly overrun, which could be attributed to anthropogenic changes/impacts accordingly to Catianis [ 68 ]. Over the years, previous studies of the Black Sea mussels have also reported slightly excessive Pb concentrations in that area [ 37 , 69 ], and the evolution trends were not very clear due to large concentration fluctuations [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…1881/2006 [ 49 ], and there are no concerns about their consumption, especially when calculated hazard quotients were below the critical value 1 for all analyzed heavy metals, meaning no possible risks are associated with mussel consumption from the study areas. However, Pb concentrations in mussel meat samples taken from area 3 have slightly overrun, which could be attributed to anthropogenic changes/impacts accordingly to Catianis [ 68 ]. Over the years, previous studies of the Black Sea mussels have also reported slightly excessive Pb concentrations in that area [ 37 , 69 ], and the evolution trends were not very clear due to large concentration fluctuations [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study area, the influence of the Danube freshwater extends to the south, towards Mangalia, due to the longshore current oriented from the Danube Delta to south, and also to the deep-sea zone (Panin and Jipa, 2002;Catianis et al, 2016;Constantinescu et al, 2023). Moreover, the Danube sandy sediments are remobilized from north to south, due to the longitudinal marine coastal current (Catianis et al, 2016).…”
Section: Study Areamentioning
confidence: 97%
“…In the study area, the influence of the Danube freshwater extends to the south, towards Mangalia, due to the longshore current oriented from the Danube Delta to south, and also to the deep-sea zone (Panin and Jipa, 2002;Catianis et al, 2016;Constantinescu et al, 2023). Moreover, the Danube sandy sediments are remobilized from north to south, due to the longitudinal marine coastal current (Catianis et al, 2016). The jetties of the ports of Sulina, Midia, Constanta, and Mangalia are major obstacles for the transport of sediments, which are either deposited near the ports or redirected offshore (Ungureanu and Stanica, 2000).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations